Effect of synthesis method on ammonium sorption behavior of oat husk biochar - José Daniel da Silva Fonseca; Karolina Matej-Łukowicz; Jacek Kluska; Mateusz Adam Baluk; Joanna Kulesza; Bráulio Silva Barros; Ewa Wojciechowska (Scientific Reports)
Abstract Ammonium is a pollutant commonly detected in various water sources and, in high concentrations, poses significant risks to environmental quality and public health. Numerous techniques have been developed and are currently employed to eliminate pollutants, including ammonium ions, from water. Among these various methods, adsorption has proven to be the most cost-effective and eco-friendly, particularly when utilizing an inexpensive and effective adsorbent. This study aims to determine the optimal method for producing biochar from oat husks, focusing on maximizing ammonium adsorption capacity among three selected preparation techniques. The chosen methods are based on a common combustion process and the use of chemical activators, such as ferrocene and sodium hydroxide. Biochar produced with sodium hydroxide exhibited the highest concentration of oxidized groups, as confirmed by Fourier transform infrared (FTIR) spectroscopy. The adsorption kinetics of ammonium via the sodium hydroxide-modified biochar followed the Avrami model. The adsorption isotherms were best described by the Freundlich (R2 > 0.9) and Langmuir (R2 > 0.8) models. The desorption behavior followed a first-order model. According to the Langmuir isotherm, the maximum adsorption capacity of the NaOH-modified biochar was 59.61 mg/g. The method utilizing sodium hydroxide was the most effective at preparing biochar with the highest adsorption capacity, indicating its potential applicability in the remediation of ammonium-contaminated water. This research also establishes a foundation for further investigation into methods for producing biochar with enhanced adsorption capabilities from the same agricultural waste source.